Measuring hardness distribution of cooked rice by single-grain puncture - Perez, Consuelo M.; BOURNE, MALCOLM C.; Juliano, Bienvenido O. (Wiley, 1996)
A 0.71‐mm‐diameter punch mounted in the Instron Universal Testing Machine was used to measure hardness of 100 individual grains of 15 rices after cooking. A hardness distribution curve for each rice was obtained. The puncture forces of rices cooked at a fixed water:rice weight ratio of 2 were more variable than those for rices cooked in excess water for the optimum cooking time. High‐ and intermediate‐amylose rices cooked using a water:rice ratio of 2 were harder than corresponding rices cooked in excess water. For waxy and low‐amylose rices, the reverse was generally true. Pairs of rices with almost identical physicochemical properties but which differed in preference tests by consumers also differed in their hardness distribution profile.